788. Risk Factors for Severe COVID-19 Breakthrough Infections: A Retrospective, Nationwide Cohort Study. (15th December 2022) - Vo, Austin D; Branch-Elliman, Westyn; La, Jennifer; Ronan, Matthew; Brophy, Mary; Wu, Julie; Do, Nhan; Strymish, Judith; Fillmore, Nathanael; Monach, Paul
Abstract: Background: COVID-19 vaccines reduce the incidence of severe clinical outcomes, however, some patients remain at risk of severe disease. The primary aim of this large, nationwide retrospective cohort was to identify risk factors for severe disease despite vaccination. Methods: Nationwide cohort study of US Veteran patients with laboratory-confirmed SARS-CoV-2 infection after vaccination. The primary outcome was development of severe COVID-19 disease, defined as a hospitalization within 14 days of a positive SARS-CoV-2 diagnostic test and either SpO2 ≤ 94%, receipt of supplemental oxygen, mechanical ventilation, or death within 28 days. Exposure variables included demographic and clinical risk factors, receipt of an additional vaccine dose, and calendar months since initial vaccination series. Data were analyzed using logistic regression, and adjusted odds ratios (aORs) are presented. Results: Among 111, 151 breakthrough infections, 110, 760 had disease severity assessments and were included. 14, 690/110, 790 (13.3%) were hospitalized with severe COVID-19 or died. Risk factors for severe disease are presented in Figure 1. The strongest risk factor for severe disease despite vaccination was age. Immunocompromising conditions, including immunosuppressive medications (Cytokine-blocking, aOR, 1.73, CI, 1.37–2.18; receipt of glucocorticoids, aOR, 2.41, CI, 2.25, 2.58; leukocyte inhibitory, aOR 2.44, CI, 1.98–2.99; lymphocyte-depleting, aOR, 2.12, 1.61–2.79), cytotoxic chemotherapy within 6 months (aOR, 2.69; CI, 2.25, 3.21), and leukemias/lymphomas were also associated with increased risk (aOR, 1.84, CI, 1.59–2.14), as were chronic conditions associated with end-organ disease. Receipt of an additional (booster) dose of vaccine was associated with reduced odds of severe disease, with risk reduction from vaccination and boosting strongest during the months immediately following vaccine doses. Figure 1. Adjusted Odds of Severe Breakthrough Infection in a Large, Nationwide Cohort of US Veteran Patients Variables with aOR <1 are associated with reduced odds of severe breakthrough infections and variables with aOR >1 are associated with increased odds of severe breakthrough infections. Referent groups for multicategory variables are listed in bold. Presented with a logarithmic scale. Conclusion: In this nationwide cohort, we identified risk factors for severe disease despite vaccination. Findings can be used to inform outreach efforts for booster vaccinations and to inform clinical decision making about risk and to identify patients who would benefit from interventions in addition to vaccination, such as pre-exposure prophylaxis and antiviral therapy. Disclosures: Westyn Branch-Elliman, MD, MMSc, DLA Piper, LLC/Medtronic: Advisor/Consultant|Gilead Pharmaceuticals: Grant/Research Support Paul Monach, MD, PhD, Celgene / Bristol-Myers Squibb: Advisor/Consultant|ChemoCentryx: Advisor/Consultant|Gilead: Grant/Research Support|Kiniksa: Advisor/Consultant.